Optimalisasi Kompetensi Dosen Pembimbing dalam Meningkatkan Kualitas Lulusan Taruna Tingkat III/Sermatar Prodi Teknik Sipil Pertahanan Akademi Militer Magelang - Madyasari Suryaningrum; Yunita Fitri Wahyuningtyas (Lembaga Pengembangan Kinerja Dosen, 2026)
The management of academic human resources is a strategic factor in ensuring graduate quality, including within the context of military education at the Indonesian Military Academy (Akmil) Magelang. One crucial aspect of academic governance is the effectiveness of thesis supervisors in guiding cadets during the final project process as a mechanism for controlling learning outcome quality. Recent educational policy changes, particularly the reduction of the study period and the assignment of cadets to military units after commissioning, have created managerial challenges in supervising academic guidance systems, especially in the Defense Civil Engineering Study Program. This study aims to analyze the optimization of supervisors’ competencies as part of academic supervision management in supporting the quality of third-level cadet graduates (Sermatar). A descriptive qualitative approach was employed, with data collected through in-depth interviews, observations, and document analysis involving supervisors and cadets. Data were analyzed using the interactive model of Miles and Huberman. The findings indicate that pedagogical, professional, personal, and social competencies of supervisors have been adequately managed and implemented within the final project supervision system. However, several constraints remain, including limited time availability, the absence of fully standardized supervision mechanisms, and limited capacity-building opportunities for supervisors. Therefore, strengthening supervision governance through standardized procedures, continuous competency development, and the utilization of technology is necessary as part of an academic human resource management strategy to maintain and enhance the quality of cadet graduates.